2010
DOI: 10.1029/2009ja014932
|View full text |Cite
|
Sign up to set email alerts
|

Generation of whistler mode emissions in the inner magnetosphere: An event study

Abstract: [1] On July 24, 2003, when the Cluster 4 satellite crossed the magnetic equator at about 4.5 R E radial distance on the dusk side (∼15 MLT), whistler wave emissions were observed below the local electron gyrofrequency (f ce ) in two bands, one band above one-half the gyrofrequency (0.5f ce ) and the other band below 0.5f ce . A careful analysis of the wave emissions for this event has shown that Cluster 4 passed through the wave source region. Simultaneous electron particle data from the PEACE instrument in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 70 publications
4
48
0
Order By: Relevance
“…Our simulation reinforces basic results of Liu et al [2011]: that the warm and hot components drive the upper and lower chorus bands, respectively, and that at least through time of saturation linear instability growth determines the dynamics with no evidence for nonlinear coupling between the spectra of the two bands [cf. Schriver et al , 2010]. Our simulation also reinforces fundamental conclusions of Gary et al [2011] that electromagnetic whistler fluctuations reduce the electron component anisotropy through pitch angle scattering, whereas quasi-electrostatic whistlers can scatter electrons into the high-speed tail of the parallel velocity distribution through Landau resonance.…”
Section: Particle-in-cell Simulationsupporting
confidence: 88%
See 1 more Smart Citation
“…Our simulation reinforces basic results of Liu et al [2011]: that the warm and hot components drive the upper and lower chorus bands, respectively, and that at least through time of saturation linear instability growth determines the dynamics with no evidence for nonlinear coupling between the spectra of the two bands [cf. Schriver et al , 2010]. Our simulation also reinforces fundamental conclusions of Gary et al [2011] that electromagnetic whistler fluctuations reduce the electron component anisotropy through pitch angle scattering, whereas quasi-electrostatic whistlers can scatter electrons into the high-speed tail of the parallel velocity distribution through Landau resonance.…”
Section: Particle-in-cell Simulationsupporting
confidence: 88%
“…Santolík et al [2010] used kinetic linear dispersion theory to study a banded chorus case observed by the Cluster spacecraft and showed that highly anisotropic ( T ⊥ / T ∥ >10) injected electrons at energies of a few hundred eV to a few keV could drive the upper band chorus; but their model of trapped electrons at energies above 10 keV gave insufficient growth of the lower band. A related particle-in-cell (PIC) simulation by Schriver et al [2010] also based on Cluster electron observations showed that 300 eV anisotropic electrons indeed drove upper band whistlers unstable but that the lower band is generated by nonlinear wave-wave coupling. Liu et al [2011] carried out further PIC simulations based upon typical magnetospheric parameters showing that warm (below 1 keV) and hot (above 10 keV) electron components with sufficiently large temperature anisotropies could drive both lower band and upper band whistler instabilities relatively independent of each other.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the injected electrons at lower energies could be responsible for a part of the waves that propagate obliquely at frequencies above f ce /2 and suggested that a nonlinear generation mechanism might be necessary to explain the waves below f ce /2. Schriver et al (2010) used the same Cluster event and data as part of a theoretical study of the wave generation. Their theoretical results showed that the anisotropic electron distribution could linearly excite obliquely propagating whistler-mode chorus waves in the upper frequency band (>f ce /2).…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
“…Darwin PIC model has been used previously to study the whistler anisotropy instability in the solar wind 33 and Earth's inner magnetosphere 34,35 . Compared to a conventional electromagnetic PIC method, the Darwin PIC method excludes the transverse component of the displacement current in Ampere's law and hence excludes retardation effects and light waves, but leaves the physics of whistler waves unaffected [36][37][38] .…”
Section: Computational Setupmentioning
confidence: 99%